Curcumin- and resveratrol-co-loaded nanoparticles in synergistic treatment of hepatocellular carcinoma - Yongshun Zheng; Ran Jia; Jun Li; Xiaohe Tian; Yeben Qian (Journal of Nanobiotechnology, 2022)
Abstract Background Currently, systemic therapies for patients with advanced-stage hepatocellular carcinoma (HCC) rely mainly on systemic drugs. However, traditional systemic drugs have a high rate of serious adverse events, and the curative effects of some potential anticancer drugs, such as curcumin (CUR) and resveratrol (RSV), are less apparent due to their poor bioavailability. Therefore, it is urgent to develop a highly effective therapy to improve patient prognosis. Herein, an injectable HCC-targeted nanoparticle (NP) was designed to deliver CUR and RSV to hepatoma cells. Results The molecular self-assembled NPs showed higher tumour retention through the enhanced permeability and retention (EPR) effect of the NPs and surface modification with the HCC-specific peptide moiety SP94 to effectively treat HCC. These HCC-targeted NPs led to a significant reduction in the drug dosage, delayed the rate of drug release and improved the bioavailability of the encapsulated drugs. The drug concentrations in the vicinity of the tumour increased, and a good therapeutic effect was observed without obvious side effects. Conclusions These SP94-mediated NPs allowed large amounts of antitumor drugs to accumulate in tumours, providing a novel strategy for innovative HCC therapy. This nanoplatform also offers an idea for exploring other potential chemotherapeutics. Graphical Abstract